Cu-catalyzed coupling of unactivated tertiary alkyl alcohols with thiols via C–O bond cleavage. (19th January 2022) - Xu, Bing; Ye, Yang; Lin, Ying; Bai, Renren; Ye, Xiang-Yang; Xie, Tian
Graphical abstract: Abstarct: Herein we present the plain manufacture of sterically hindered tertiary alkyl thioethers via the Cu-catalyzed coupling of unactivated tertiary alkyl alcohols with thio-alcohols/phenols. The present strategy with easy-to-operate reaction conditions represents one of the most effective unactivated tertiary C(sp 3 )–S bond-forming methods via readily accessible Lewis acid catalysis. Moreover, this protocol has high functional group compatibility and wide substrate adaptability.